Respostas

A melhor resposta!
2013-07-02T16:59:56-03:00

√(2x) = 1+ √(x+7)

√(2x) - 1=√(x+7)

(√(2x) - 1)²=(√(x+7))²

2x-2√(2x)+1=x+7

2x+1-x-7=2√(2x)

x-6=2√(2x)

(x-6)²=(2√(2x))²

x²-12x+36=8x

x²-20x+36=0

delta=400-144

delta=256

x=(20+/-16)/2

x1=18

x2=2

Como temos raízes envolvidas na equação temos que conferir os dois resultados na equação original.

√(2(18)) = 1+ √((18)+7)

√(36) = 1+ √(25)

6=1+5

6=6 verdadeiro

√(2(2)) = 1+ √((2)+7)

√(4) = 1+ √(9)

2=1+3

2=4 falso

resposta:x=18

2 5 2